An intelligent decision-making system for embryo transfer in reproductive technology: a machine learning-based approach - Badr, Sanaa; Tahri, Meryem; Maanan, Mohamed; Kašpar, Jan; Yousfi, Noura (Systems biology in reproductive medicine, 2025)
Infertility has emerged as a significant public health concern, with assisted reproductive technology (ART) is a last-resort treatment option. However, ART's efficacy is limited by significant financial cost and physical discomfort. The aim of this study is to build Machine learning (ML) decision-support models to predict the optimal range of embryo numbers to transfer, using data from infertile couples identified through literature reviews. Binary classification models were developed to classify cases into two groups: those transferring two or fewer embryos and those transferring three or four. Four popular ML algorithms were used, including random forest (RF), logistic regression (LR), support vector machine (SVM), and artificial neural network (ANN), considering seven criteria: the woman's age, sperm origin, the developmental qualities of four potential embryos, infertility duration, assessment of the woman, morphological qualities of the four best embryos on the day of transfer, and number of oocytes extracted. The stratified 3-fold cross-validation results show that the SVM model obtained the highest average accuracy (95.83%) and demonstrated the best overall performance, closely followed by the ANN and LR models with an average accuracy equal to 91.67%. The RF model achieved a slightly lower average accuracy (88.89%), which demonstrated the lowest variability. Testing on a new dataset revealed all models performed well, with ANN and SVM models classified all test set instances correctly, while the RF and LR models achieved 91.68% accuracy. These results highlight the superior generalization and effectiveness of the ANN and SVM models in guiding ART decisions.
Keywords: Embryo Transfer; embryo transfer; Pregnancy; Humans; Support Vector Machine; Artificial neural network; number of embryos; support vector machine; neuronové sítě; Female; dospělí; Machine Learning; přenos embrya; multi-criteria decision aiding; Neural Networks, Computer; lidé; infertilita; Adult; assisted reproductive technology; ženské pohlaví; strojové učení; Male; těhotenství; Reproductive Techniques, Assisted; asistovaná reprodukce; mužské pohlaví; infertility; Infertility